A case of cavernous sinus thrombosis caused by Dialister pneumosintes, Slackia exigua and Prevotella baroniae. Issue 3 (September 2014) - Matsumura, Hideaki; Suzuki, Hiromichi; Ito, Yoshiro; Kino, Hiroyoshi; Tamai, Kiyoko; Notake, Shigeyuki; Nakamura, Kazuhiro; Shiigai, Masanari; Uemura, Kazuya; Matsumura, Akira
Abstract : Introduction: Cavernous sinus thrombosis (CST) is a rare manifestation of cerebral venous thrombosis. We herein describe the first case of CST associated with the oral microbes (Dialister pneumosintes, Slackia exigua and Prevotella baroniae). Case presentation: An 82‐year‐old previously self‐supported Japanese woman presented with acute onset of impaired consciousness. Computed tomography revealed intracranial haemorrhage complicated with CST. D. pneumosintes, Slackia exigua and P. baroniae were cultivated from two sets of blood cultures and were identified with 16S rRNA sequencing. The patient was successfully discharged after ampicillin–sulbactam treatment, which was performed soon after admission. Conclusion: To our knowledge, this is the first description of CST caused by D. pneumosintes, Slackia exigua and P. baroniae . CST should be considered in cases of unusual distribution of cerebral haemorrhage.